Gaussian and non-Gaussian limit distributions of estimates of the regression coefficients of a long-memory time series - Leonenko, N. N.; Sharapov, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain Gaussian and non-Gaussian distributions of estimates of regression coefficients of a long-memory time series.